Engineering Fe–N Coordination Structures for Fast Redox Conversion in Lithium–Sulfur Batteries. Issue 30 (19th June 2021) - Ma, Cheng; Zhang, Youquan; Feng, Yiming; Wang, Ning; Zhou, Liangjun; Liang, Chaoping; Chen, Libao; Lai, Yanqing; Ji, Xiaobo; Yan, Chenglin; Wei, Weifeng
Abstract: Critical drawbacks, including sluggish redox kinetics and undesirable shuttling of polysulfides (Li2 S n, n = 4–8), seriously deteriorate the electrochemical performance of high‐energy‐density lithium–sulfur (Li–S) batteries. Herein, these challenges are addressed by constructing an integrated catalyst with dual active sites, where single‐atom (SA)‐Fe and polar Fe2 N are co‐embedded in nitrogen‐doped graphene (SA‐Fe/Fe2 N@NG). The SA‐Fe, with plane‐symmetric Fe‐4N coordination, and Fe2 N, with triangular pyramidal Fe‐3N coordination, in this well‐designed configuration exhibit synergistic adsorption of polysulfides and catalytic selectivity for Li2 S n lithiation and Li2 S delithiation, respectively. These characteristics endow the SA‐Fe/Fe2 N@NG‐modified separator with an optimal polysulfides confinement–catalysis ability, thus accelerating the bidirectional liquid–solid conversion (Li2 S n ↔Li2 S) and suppressing the shuttle effect. Consequently, a Li–S battery based on the SA‐Fe/Fe2 N@NG separator achieves a high capacity retention of 84.1% over 500 cycles at 1 C (pure S cathode, S content: 70 wt%) and a high areal capacity of 5.02 mAh cm −2 at 0.1 C (SA‐Fe/Fe2 N@NG‐supported S cathode, S loading = 5 mg cm −2 ). It is expected that the outcomes of the present study will facilitate the design of high‐efficiency catalysts for long‐lasting Li–S batteries. Abstract : An integrated catalyst comprising single‐atom Fe and Fe2 N composite sites, with dual‐tailed Fe–N coordination structures, co‐decorated on N‐doped graphene is successfully constructed and demonstrated. The catalyst optimizes the polysulfide absorption–catalysis behavior, thereby facilitating fast redox conversion and suppressing the shuttle effect. Consequently, the Li–S batteries exhibit high‐energy and long‐cycling stability.